2017
DOI: 10.1177/1536012117704768
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent, Plasmonic, and Radiotherapeutic Properties of the 177Lu–Dendrimer-AuNP–Folate–Bombesin Nanoprobe Located Inside Cancer Cells

Abstract: The integration of fluorescence and plasmonic properties into one molecule is of importance in developing multifunctional imaging and therapy nanoprobes. The aim of this research was to evaluate the fluorescent properties and the plasmonic–photothermal, therapeutic, and radiotherapeutic potential of 177Lu–dendrimer conjugated to folate and bombesin with gold nanoparticles in the dendritic cavity (177Lu–DenAuNP–folate–bombesin) when it is internalized in T47D breast cancer cells. The intense near-Infrared (NIR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…The entrapped AuNPs provided photophysical properties to the whole nanoconjugate suitable for optical imaging. The final nanoconjugate was labeled with 177 Lu, seeking for multimodal platforms suitable for breast cancer cell targeting [128,129]. The radiolabeled nanoconjugate showed specific uptake in breast cancer T47D cells and provided suitable optical images.…”
Section: Lutetium-177mentioning
confidence: 99%
“…The entrapped AuNPs provided photophysical properties to the whole nanoconjugate suitable for optical imaging. The final nanoconjugate was labeled with 177 Lu, seeking for multimodal platforms suitable for breast cancer cell targeting [128,129]. The radiolabeled nanoconjugate showed specific uptake in breast cancer T47D cells and provided suitable optical images.…”
Section: Lutetium-177mentioning
confidence: 99%
“…Preliminary in vitro studies in T47D breast cancer cells showed a specific cell uptake (41.15% ± 2.72%), which can be potentially used for targeted RT of breast tumors overexpressing GRPR and FAR. In another work, the same authors attempted to combine fluorescence imaging capability and plasmonic‐photothermal property owing to the entrapment of Au NPs within the dendritic cavity with radiotherapeutic potential. After the 177 Lu‐labeled dendrimeric nanodevices were internalized into T47D breast cancer cells, the intense near‐Infrared (NIR) fluorescence emitted at 825 nm from the conjugate inside cells corroborated the usefulness of DenAuNP–folate–bombesin for optical imaging.…”
Section: Radiolabeled Dendrimer‐based Nanodevices For Rt and Theranosmentioning
confidence: 99%
“…Bombesin and folic acid were covalently conjugated onto the dendrimers via their carboxylate groups, and were consequently radiolabeled with 177 Lu, via the chelator S-2-[4-Isothiocyanatobenzyl]-1,4,7,10-tetraazacyclododecane tetraacetic acid (p-SCN-benzyl-DOTA). Results of T47D tumor cells treated with this complex showed an outstanding decrease in cell viability up to 90% [103]. A combo treatment of breast and pancreatic cancer was devised, consisting of two separate systems; an anticancer agent called cyclopamine (CPA) combined with liquid-lipid nanoparticles (LLP) and radiolabeled 177 Lu into lipid-calcium-phosphate (LCP) nanoparticles and studied the effect of increased radioisotope on the properties of the nanosystem.…”
Section: Lutetium-177mentioning
confidence: 99%